My alternate life - McClain, Lee. (New York, N.Y. Smooch, 2004)
Thanks to a mysterious computer game, urban tough girl Trinity B. Jones has the chance to live her alternate life.
"Smooch teen fiction"--Spine.
Keywords: Teenage girls -- Juvenile fiction; Adopted children -- Juvenile fiction; Teenage girls -- Fiction; Adopted children -- Fiction; Young adult fiction